Ergonomic-Based Redesign of Broomsticks Reduces the Physiological Burdens of Street Sweepers in Denpasar City, Indonesia - Palilingan, Richard Andreas; Tirtayasa, Ketut; Surata, I Wayan (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
The equipment, such as broomsticks used by street sweepers are not appropriate based on anthropometric aspects, with a potency to induce inconvenience among them. Working with equipment that is not ergonomics, in addition to non-physiological work posture can cause fatigue, musculoskeletal disorders, and increased workload. This study aims to determine whether redesign an ergonomic-based broomstick may reduce the physiological burden of street sweepers in Denpasar city, Indonesia. This research is a pure experiment using a cross-design (two-period crossover design). The sample was 16 female street sweepers, divided into two groups: 8 as the control group and 8 treatment groups. Data analysis were performed using a paired t-test with significance level of 5%. The results showed significant difference (p <0.05) on the variables of workload, musculoskeletal complaints, and fatigue. In the first period, the mean of the street sweeper working heart rate was 118.96 ± 2.26 beats per minutes (bpm), the mean musculoskeletal complaint score was 91.63 ± 2.70 and the average fatigue was 77.69 ± 2.96. In Period II, the mean heart rate was 98.49 ± 2.22 bpm, the mean musculoskeletal complaint score was 63.56 ± 2.73 and the average fatigue was 57.56 ± 2.94. Redesigned stem brooms turned out to reduce workload, musculoskeletal complaints, and fatigue by 17.21%, 30.6%, and 25.91%, respectively. It can be concluded that the redesign of an ergonomic-based broomstick can reduce workload, musculoskeletal complaints, and fatigue.